Direct Medical Cost Analysis Among Coronary Heart Disease and Heart Failure Outpatients at One Hospital - Nunik Dewi Kumalasari; Abdul Rahem; Bobby Presley; Eko Setiawan (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Long-term treatment of cardiovascular disease may give impact in a high burden of medical cost for the patient. A concern arises whether the health budget allocation prepared by the Indonesian Government through "Jaminan Kesehatan Nasional" program is enough to cover medical cost for the outpatient treatment. This study aims to calculate the direct medical cost of patients with coronary heart disease and heart failure and compare it with the Indonesian Case Base Groups (INA-CBGs) tariff. This is a prospective and observational study carried out in one of the public hospitals in East Java between February and April 2015. All data related to outpatients with coronary heart disease and heart failure were analysed. Direct medical cost analysis in this study calculated from a combination of cost of medication, health professional services, electrocardiography, emergency care services, and laboratory test component, then it was compared with INA-CBGs tariff from ICD 10. Total of 390 patients included were 387 patients with coronary heart disease (99.23%) and three (3) patients with heart failure (0.77%). Average direct medical cost for patients with coronary heart disease and heart failure were IDR 130.593,6 (range IDR 50.282 – IDR 385.911) and IDR 128.587 (range IDR 112.832 – IDR 140.103), respectively. Even though this study showed that budget allocation of INA-CBGs could cover the average direct medical cost of patients with both of diseases, some patients had a direct medical cost higher than the limit of INA-CBGs allocation. Therefore, an optimal interprofessional collaboration between physician and pharmacist needed to provide medical treatment based on patient needs and keep it within budget allocation range.